Exploring the relationships between criminal self-efficacy factors and recidivism - Ung, Jamie (Legal and criminological psychology, 2024)
Purpose Criminal self-efficacy, an antisocial belief representing positive appraisal of one's capabilities to enact crime, is theorized to drive criminal behaviour, but few measures exist. Our aim was to re-validate one measure of criminal self-efficacy by re-testing its ability to predict recidivism. Methods We used Criminal Self-efficacy Scale-15 scores from 353 people on community corrections orders measured up to three times. Results Confirmatory factor analysis revealed three latent factors we called criminal connections, physical violence, and criminal expertise. Cox regression survival analysis demonstrated that only physical violence scores predicted recidivism. Conclusions The three factors provide a meaningful conceptual basis for future attempts to develop measures of criminal self-efficacy that improve on the limitations of current measures. More broadly, there is a need to understand how specific antisocial beliefs such as criminal self-efficacy are related to criminal behaviour.